2016
DOI: 10.1016/j.engstruct.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

“Time-building specific” seismic vulnerability assessment of a hospital RC building using field monitoring data

Abstract: 14In the context of seismic vulnerability assessment of reinforced concrete (RC) buildings, the use 15 of field monitoring data constitutes a significant tool for the representation of the actual structural state, 16reducing uncertainties associated with the building configuration properties as well as many non-17 physical parameters (age, maintenance, etc.), enhancing thus the reliability in the risk assessment 18 procedure. In this study, the seismic vulnerability of existing RC buildings is evaluated, combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 54 publications
0
17
0
2
Order By: Relevance
“…Fragility function quantifies the probability of selected system responses exceeding a given damage measure (DM) at a specified ground motion intensity and it is a probabilistic approach to conduct the vulnerability and risk assessment of subway station structures. Traditionally, fragility curves have been established for buildings (Brunesi et al, 2015b;Kiani et al, 2016;Park and Kim, 2010), and improved fragility analysis methods are also proposed for surface structure (Banerjee et al, 2016;Karapetrou et al, 2016;Mandal et al, 2016). In this article, fragility analysis is extended to the lifeline system of the subway station structure during which a probabilistic framework is developed.…”
Section: Introductionmentioning
confidence: 99%
“…Fragility function quantifies the probability of selected system responses exceeding a given damage measure (DM) at a specified ground motion intensity and it is a probabilistic approach to conduct the vulnerability and risk assessment of subway station structures. Traditionally, fragility curves have been established for buildings (Brunesi et al, 2015b;Kiani et al, 2016;Park and Kim, 2010), and improved fragility analysis methods are also proposed for surface structure (Banerjee et al, 2016;Karapetrou et al, 2016;Mandal et al, 2016). In this article, fragility analysis is extended to the lifeline system of the subway station structure during which a probabilistic framework is developed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ShakeMap system (Worden and Wald 2016) of the USGS provides GM data, which take into consideration information from recording stations and observed damage. For single structures, health-monitoring techniques using ambient noise or small earthquake records can be used to update the numerical model, which can lead to an improvement of the fragility functions (Karapetrou et al 2016). Exposure data can be accessed through large-scale initiatives, such as Hazus (also covering Canada), H2020 European projects project Seismology and Earthquake Engineering Research Infrastructure Alliance (SERA), the European Plate Observing System (EPOS) initiative, and the Global Earthquake Model.…”
Section: Lack Of Expertise In Loss Modelingmentioning
confidence: 99%
“…It was concluded that the results obtained from the ambient vibration could be used to produce more reliable models based on their existing conditions. Furthermore, Karapetrou et al (2016) presented a comprehensive methodology for utilizing the obtained field data for a structure, i.e. dynamic properties, in the derivation of time dependent fragility curves.…”
Section: Seismicmentioning
confidence: 99%